INFLUENCE OF COUNSELING ABOUT COLOSTRUM ON THE KNOWLEDGE OF PREGNANT WOMEN IN PMB MOJOROTO DISTRICT KEDIRI CITY - Uskenat, Kristavera (Jurnal Mahasiswa Kesehatan, 2021)
One of the causes of high infant mortality is malnutrition, which can be avoided by breastfeeding, starting with colostrum. Colostrum is the first breast milk to supply various immune and growth factors to ensure the survival and health of the newborn. The research objective was to determine the effect of counseling on colostrum on the knowledge of pregnant women at PMB Ny. "E" Bandar Lor, Mojoroto Subdistrict, Kediri City in 2020.The design used in this study was a pre-experimental design with a one group pre test post test approach, the population studied were all pregnant women in PMB Ny. "E" amounted to 55 people with a purposive sampling technique obtained a sample of 20 people. Treatment is the provision of counseling. The instrument used is a questionnaire sheet. This study uses the Wilcoxon Rank Test statistical test. Based on the analysis using the Wilcoxon Rank Test statistical test with a p value of 0.00 <α = 0.05. From the positive ranks value 19ᵇ, the negative rank value is 0ᵃ, and ties value is 1ᶜ. This means that there is an effect of counseling about colostrum on the knowledge of pregnant women at PMB Ny. "E". Counseling about colostrum has an influence on the knowledge of pregnant women. It is hoped that health workers will motivate pregnant women to know about Colostrum.